Benin : Second Review Under the Three-Year Arrangement Under the Extended Credit Facility and Request for a Waiver of the Nonobservances of a Continuous Performance Criterion: Staff Report; Staff Supplement; Press Release; and Statement by the Executive Director for Benin. (IMF Staff Country Reports; Country Report ;, 2011)
Despite severe economic, political, and natural setbacks in Benin in 2010, its economic growth has accelerated in 2011. The Executive Board of the International Monetary Fund (IMF) has appreciated Benin's economic performance under the program supported by the Extended Credit Facility (ECF). Based on the satisfactory performance and strong policy commitments, the Executive Board has granted a waiver for Benin. Directors have emphasized that a prudent fiscal policy is essential to preserve macroeconomic stability.